Fibre reinforcement in a structurally compromised endodontically treated molar: a case report - Renita Soares; Ida de Noronha de Ataide; Marina Fernandes; Rajan Lambor (Korean Academy of Conservative Dentistry, 2016)
The reconstruction of structurally compromised posterior teeth is a rather challenging procedure. The tendency of endodontically treated teeth (ETT) to fracture is considerably higher than vital teeth. Although posts and core build-ups followed by conventional crowns have been generally employed for the purpose of reconstruction, this procedure entails sacrificing a considerable amount of residual sound enamel and dentin. This has drawn the attention of researchers to fibre reinforcement. Fibre-reinforced composite (FRC), designed to replace dentin, enables the biomimetic restoration of teeth. Besides improving the strength of the restoration, the incorporation of glass fibres into composite resins leads to favorable fracture patterns because the fibre layer acts as a stress breaker and stops crack propagation. The following case report presents a technique for reinforcing a badly broken-down ETT with biomimetic materials and FRC. The proper utilization of FRC in structurally compromised teeth can be considered to be an economical and practical measure that may obviate the use of extensive prosthetic treatment.